Similarities and Differences of the Emerging Prison Problems in England and Wales vs. Kosovo: a Sociological and Criminological Perspective - Lubach, MSc. Arben (Iliria international review, 2015)
Prisons are probably the most debatable institutions within the Criminal Justice System in any given country and as such demand contemporary explanation and understanding. Despite the fact that prisons affect the life of many people, not only of those incarcerated but also of their families and friends, nevertheless they do not receive the necessary attention; instead they remain the most enigmatic and less interesting organizations amongst the Criminal Justice System in general.This paper, by using a literature review approach, looks into some of the most important debates, similarities and differences respectively, about prisons in England and Wales, and Kosovo. Whilst most of the problems both countries face are of similar nature, Kosovo nevertheless faces some additional problems which are not visible in the England and Wales prisons. The paper further examines the causes of these problems in the Kosovo prisons and the involvement of the international community and their efforts in assisting Kosovo in fixing the problems in the field of corrections as part of the Kosovo state-building process.The paper will show that both countries face difficulties with similar problem areas such as overcrowding, running costs, and so on. However, compared to England and Wales, the problems Kosovo prison system is facing are of a more serious and complicated nature which require serious involvement of the Kosovo government and policy makers as well as the international community which has been present in Kosovo since 1999